2021
DOI: 10.7759/cureus.19416
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in the Management of Refractory Myasthenia Gravis and Variability of Its Efficacy in Anti-MuSK Positive and Anti-AChR Positive Myasthenia Gravis

Abstract: Myasthenia gravis affects the neuromuscular junction of the skeletal muscles. It results in muscle weakness involving skeletal muscles (diaphragm, extraocular muscles) and myasthenic crisis. Treatment options for myasthenia gravis management have expanded, including azathioprine, corticosteroids, plasma exchange, and tacrolimus. Unfortunately, a few cases of myasthenia gravis don't respond to conventional treatment modalities. Monoclonal antibodies, rituximab (RTX), are novel treatments that have garnered inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…Since then, case reports and small-sample studies on RTX treatment in refractory MG have been endlessly streaming ( 55 58 ). Although it was not supported by advanced evidence-based medical studies, it has been widely applied in the clinical field, and these studies reflected the effectiveness of RTX in patients with anti-Musk positive and some anti-AChR positive MG ( 59 , 60 ). The second co-cited paper titled “myasthenia gravis” was published by Vincent A ( 38 ), and was published in Lancet in 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, case reports and small-sample studies on RTX treatment in refractory MG have been endlessly streaming ( 55 58 ). Although it was not supported by advanced evidence-based medical studies, it has been widely applied in the clinical field, and these studies reflected the effectiveness of RTX in patients with anti-Musk positive and some anti-AChR positive MG ( 59 , 60 ). The second co-cited paper titled “myasthenia gravis” was published by Vincent A ( 38 ), and was published in Lancet in 2001.…”
Section: Discussionmentioning
confidence: 99%
“… 24 This may be due to bias in patient selection. RTX also has beneficial effects in refractory MG. 25 In a prospective study by Fatehi et al, 34 patients with refractory MG had significant decreases in Myasthenia Gravis Composite (MGC) and MG-ADL scores after treatment with Zytux, an RTX biosimilar. 26 In a retrospective study with a 10-year follow-up, sustained clinical remission was achieved in all 4 patients with refractory MG after RTX therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that the efficacy of RTX may vary due to different types of antibodies. 23 , 25 In a recent study, the minimum disease state or better was achieved in 72% of MuSK-MG patients after RTX treatment, while this outcome was achieved in only 30% of AChR-MG patients. 23 This finding indicates that RTX may be more effective for MuSK-MG patients than AChR-MG patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CD20-mediated BCDT showed beneficial effects in several autoimmune diseases including multiple sclerosis, pemphigus vulgaris, rheumatoid arthritis, chronic inflammatory demyelinating polyneuropathy (CIDP) and MuSK MG [155][156][157][158][159], whereas no effect of anti-CD20-mediated BCDT therapy could be observed on the titer and clinical outcome in the majority of AChR MG patients [158,160]. Positive effects of anti-CD20-mediated BCDT have been described for severe refractory AChR MG [161,162] and the response seems better at early stages of AChR MG [163]. MG is a very heterogeneous disease [164][165][166][167].…”
Section: Anti-cd20-mediated B-cell Depletion Therapy In Myasthenia Gr...mentioning
confidence: 99%
“…showing that MuSK MG is a heterogenous disease [162,169]. The efficacy of anti-CD20-mediated BCDT has not been evaluated for MG with autoantibodies targeting LRP4 and agrin yet, while initial promising results showed a beneficial effect of anti-CD20-mediated BCDT in the case of a patient with juvenile seronegative MG [176].…”
Section: Anti-cd20-mediated B-cell Depletion Therapy In Myasthenia Gr...mentioning
confidence: 99%